Effects of weekly low-frequency rTMS on autonomic measures in children with autism spectrum disorder - Casanova, Manuel Fernando; Hensley, Marie K.; Sokhadze, Estate M.; El-Baz, Ayman S.; Wang, Yao; Li, Xiaoli; Sears, Lonnie (Frontiers in Human Neuroscience, 2014)
The term autism spectrum disorder (ASD) describes a range of conditions characterized by impairments in social interactions, communication, and by restricted and repetitive behaviors. Autism spectrum disorder may also present with symptoms suggestive of autonomic nervous system (ANS) dysfunction. The objective of this study was to determine the effect of 18 sessions of low frequency (LF) repetitive transcranial magnetic stimulation (rTMS) on autonomic function in children with ASD by recording electrocardiogram (ECG) and electrodermal activity (EDA) pre- post- and during each rTMS session. The autonomic measures of interest in this study were R-R cardiointervals in EKG (R-R), time and frequency domain measures of heart rate variability (HRV) and skin conductance level (SCL). Heart rate variability measures such as R-R intervals, standard deviation of cardiac intervals, pNN50 (percentage of cardiointervals >50 ms different from preceding interval), power of high frequency (HF) and LF components of HRV spectrum, LF/HF ratio, were then derived from the recorded EKG. We expected that the course of 18 weekly inhibitory LF rTMS applied to the dorsolateral prefrontal cortex (DLPFC) would enhance autonomic balance by facilitating frontal inhibition of limbic activity thus resulting in decreased overall heart rate (HR), increased HRV (in a form of increased HF power), decreased LF power (resulting in decreased LF/HF ratio), and decreased SCL. Behavioral evaluations post-18 TMS showed decreased irritability, hyperactivity, stereotype behavior and compulsive behavior ratings while autonomic measures indicated a significant increase in cardiac interval variability and a decrease of tonic SCL. The results suggest that 18 sessions of LF rTMS in ASD results in increased cardiac vagal control and reduced sympathetic arousal.